A robust network binder via localized linking by small molecules for high-areal-capacity silicon anodes in lithium-ion batteries. (January 2021) - Li, Zeheng; Wan, Zhengwei; Zeng, Xianqing; Zhang, Shuomeng; Yan, Lijing; Ji, JiaPeng; Wang, Hongxun; Ma, Quanxin; Liu, Tiefeng; Lin, Zhan; Ling, Min; Liang, Chengdu
Abstract: Silicon is known for high-capacity yet large-volume-change properties when used as lithium storage material. Polymeric binders substantially contribute to improving the cycling life and increasing areal capacity of silicon anode. Herein, a robust network binder (PG-c-ECH) via localized linking by small molecules is proposed to achieve stable cycling performance of silicon anode with high areal capacity. Peach gum (PG) is rich in abundant hydroxyl and carboxyl groups that conventionally ensure a strong binding affinity between the PG and Si. The epichlorohydrin (ECH) introduced as the short-chain chemical crosslinker further enhances the localized linking for the polymer chains. The resultant PG-c-ECH owns durable interfacial adhesion and outstanding mechanical properties to stabilize the structural integrity of Si anode. Graphic Abstract: Herein, a robust network binder (PG-c-ECH) via localized linking by small molecules is proposed for high-areal-capacity Si anode. Because of its strong interfacial adhesion and excellent mechanical properties, the PG-c-ECH binder could tolerate the huge volume changes of Si active materials during repeated cycling. The Si electrodes using PG-c-ECH as the binder exhibit stable cycling performances at practical-level areal capacities. ga1 Highlights: A robust network binder (PG-c-ECH) via localized linking by small molecules is proposed. The Si@PG-c-ECH electrode can be cycled over 10 mAh cm −2 for 35 cycles. The Si@PG-c-ECH electrode achieves an ultrahigh discharge areal capacity of 60.00 mAh cm −2 . The full-cell using the Si@PG-c-ECH anode shows a relatively stable cycling performance.